My brand, my self(ie) - why consumers portray themselves in brand-selfies. (14th March 2023) - Flaswinkel, Anne Mareike; Rump, Markus; Decker, Reinhold
By presenting themselves in self-portraits with brands, so-called brand-selfies (BSs), consumers can demonstrate their personal attachment to brands. A closer look at this mainstream phenomenon expands the understanding of consumer-brand relationships. The ease of sharing and networking has increased the importance of BSs in marketing. Because they reveal a lot about consumers' opinions and spread quickly on social networks, BSs can be a valuable marketing tool. In a cross-sectional study, we identify brand identification as the strongest predictor of consumers' intention to portray themselves with a brand in a BS. Furthermore, we find belonging and reward to have significant impact on the intention to post a BS. We distinguish consumer motivations for posting BSs from general motivations for posting selfies, add to previous research on selfie posting behaviour and user-generated content, and conclude with a discussion of implications for marketers looking to incorporate selfie marketing into their marketing strategy.